Prospects and problems of cognitive radio network architectures in wireless sensor networks - Salami, Abdulazeez F.; Hussaini, Mukhtar; Anwar, Farhat; Bello-Salau, Habeeb (IIUM Press, 2011)
Cognitive radio is a technique proposed by Mitola which provides a way to efficiently use precious radio spectrum resources [1, 2]. A cognitive radio recognizes, analyzes, and learns the situations of the radio spectrum and then employs various strategies to maximize spectrum usage. The concept of cognitive radio is to detect and ascertain \vhich aspect of the spectrum is presently unused, and then perform data transmission at the newly discovered frequency band. An alternative cognitive radio scheme is to transmit signals on top of existing transmissions as long as the interference temperature measure is lower than threshold. Spectrum sharing, spectrum sensing, and spectrum management are the stages of a cognitive radio. Spectrum sensing gathers up-to-date spectrum usage data, spectrum management determines the optimal spectrum access timing and scheme, and spectrum sharing ensures that users are served in a fair and timely manne